ANALISIS RESIKO KESEHATAN PENCEMARAN LOGAM BERAT PADA AIR, SEDIMEN, DAN SIMPING (Placuna placenta) DI PESISIR KABUPATEN TANGERANG - Anna Rejeki Simbolon; Etty Riani; Yusli Wardiatno (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2014)
Waste containing heavy metals originating from human activity in Tangerang will go into the waters and tributaries of the Coastal District Tangerang. Heavy metals accumulate in bodies of water, sediment and biota scallop will go into the human body through exposure to direct dermal contact or intake. The purpose of this study to determine the public health risk due to exposure to heavy metals and formulate risk management that can be done. The approach taken by the USEPA methods of risk analysis and quantification of health risks from exposure to water and sediment using SEDISOIL risk analysis model developed by the National Institute of Public Health and Environmental Protection.. The results showed that in general water quality parameters are still below the quality standard by decree No. 51 of 2004 LH. Analysis of health risks for people who move directly (bathing, swimming, fishing) shows the value of RQ > 1, meaning that coastal communities at risk for adverse effects of exposure to heavy metals Pb, Cd and Zn. Similarly, the results of the analysis of risk through consumption of biota scallop, with RQ values > 1 and ECR > 10-4. It shows that scallop (Placuna placenta) is not suitable for consumption by the public, because the content of Pd , Cd, and Zn health risk for consuming.Keywords: risk assessment, heavy metals, Tangerang District littoral